(untitled) (Research Data Journal for the Humanities and Social Sciences, 2024)
The authors describe the Qualitative Election Study of Britain (qesb) Party Leader Evaluation Database, a database containing 4,119 words and phrases evaluating British political party leaders. The data were collected during pre-election focus groups and interviews with participants from England, Scotland, and Wales during the General Election campaigns of 2010, 2015, 2017, and 2019. A supplementary dataset of leaders’ evaluation data from Dundee residents after the Scottish Independence Referendum in 2014 is also provided. To collect the data, participants viewed headshot pictures of major and minor party leaders (depending on where in Britain they lived) taken from party websites. Participants wrote down words or phrases they associated with each leader and coded their assessment as positive, negative, or neutral. These data are suitable for content, sentiment, and discourse analysis or analytic generalization.